Oxyphenbutazone-induced goitre. Issue 616 (February 1977) - Lane, R. J.; Clark, F.; McCollum, J. K.
Abstract : A woman who had taken oxyphenbutazone for 4 years because of back pain presented with goitre and hypothyroidism. This was shown to be due to an organification defect, caused or aggravated by oxyphenbutazone.